FAKTOR-FAKTOR YANG MEMPENGARUHI TERBENTUKNYA BRAND IMAGE - Hariyanto; Irma Wahyunda; Ciska Meliana Kusuma Wijaya (Dar El-Falah, 2022)
Brand image is a set of associations that consumers perceive and believe incertain products. Benefits of a positive brand image: (a) More consumersmakes purchases possible, (b) companies can develop product lines, (c)family branding policies and branding leverage can be implemented. thescope of a product's brand image: (a) service, (b) physical facilities, (c)product and service quality, (d) reputation, (e) corporate identity, (f) value.Characteristics of Brand Image, namely: (a) corporate image, (b) userimage, and (c) product image. Factors supporting the formation of brandimage are: (a) strength of brand associations, (b) Favorability of brandassociations, (c) Uniqueness of brand associations.